MENANAMKAN MENTAL ENTREPRENEURSHIP MELALUI INSTITUSI PONDOK PESANTREN (STUDI KASUS PONDOK PESANTREN RAUDLATUZZAHRAH KOLOR SUMENEP - Syaiful Anwar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2020)
Entrepreneurship is a very appropriate solution to reduce the growth rate of unemployment in our country. Because the current economic dynamics continue to accelerate and the economic arena requires us to behave creatively and innovatively. China and Japan experienced greater economic growth because the growth rate of entrepreneurs in that country exceeded 14 percent while our country according to President Jokowi was still only 3.01 percent. This really needs an acceleration in creating new entrepreneurs. This research focuses on the cultivation of mental entrepreneurship carried out by Islamic boarding schools where this institution is the oldest Islamic educational institution in Indonesia. There are two issues that the writer wants to examine further; 1) The role and strategy of the pesantren in this case the priest in instilling mental entrepreneurship in the students. 2) Constraints faced in an effort to instill mental entrepreneurship in a boarding school. The results of this study: 1) there are three strategies applied by pesantren in this case the priest in instilling mental entrepreneurship namely; counseling services and integration into extracurricular activities, self-development, and changes in learning from theory to entrepreneurship practices. 2) constraints faced; the theory applied is still not systematic, the existing facilities are not sufficient enough, and unfocusedness in learning because they still have to divide their time to study religion more.